2017
DOI: 10.1111/acem.13136
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Mentoring Practices in Academic Emergency Medicine

Abstract: Our findings help to characterize the variability of faculty mentoring in EM, identify opportunities for improvement, and underscore the need to learn from other successful mentoring programs. This study can serve as a basis to share mentoring practices and stimulate conversation around strategies to improve faculty mentoring in EM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Having new mentors shadow and then mentored by senior mentors provides training and support for new mentors [11,113,114]. Though pairing mentors to mentees was primarily mentee-initiated and based on research and career interests and/or skills [113], Bland et al (2015) reported that matching resulted in higher research activity while Shollen et al (2014) found that menteeinitiated matching resulted in increased career satisfaction. A combined matching process has been proposed as a means of reducing mismatches and failed relationships [115,116].…”
Section: Modes Of Deliverymentioning
confidence: 99%
“…Having new mentors shadow and then mentored by senior mentors provides training and support for new mentors [11,113,114]. Though pairing mentors to mentees was primarily mentee-initiated and based on research and career interests and/or skills [113], Bland et al (2015) reported that matching resulted in higher research activity while Shollen et al (2014) found that menteeinitiated matching resulted in increased career satisfaction. A combined matching process has been proposed as a means of reducing mismatches and failed relationships [115,116].…”
Section: Modes Of Deliverymentioning
confidence: 99%
“…Departments with focused mentoring programs result in increased NIH funding success, increased number of publications, and higher levels of perceived success. 22 Academic EDs that may not have NIH-funded scientists on faculty, specifically in rural areas, may have important and fundable priorities to study. Targeted interventions that extend resources to traditionally less research heavy institutions (eg, seed funding for preliminary data, and a network of available mentors willing to work with new investigators at remote sites) can create equitable opportunities for research careers across the country.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to evaluate the feasibility and effectiveness of the Step Back method for education research consultation. Given that clinician educators often face multiple competing demands for their time and may have limited local education research expertise available, this type of faculty development holds great potential to advance the field by providing instruction in education research methodology, dedicated feedback specific to an individual's project and needs, and an opportunity for collaboration and mentorship that might not have otherwise been accessible …”
Section: Discussionmentioning
confidence: 99%